PENGEMBANGAN E-MODUL BERBASIS LITERASI SAINS MATERI ORGAN GERAK HEWAN DAN MANUSIA KELAS V SD - atmaji, rizan dwi; Maryani, Ika (universitas Ahmad Dahlan, 2019)
This type of research is development research with the ADDIE model. This research begins with analysis, design, development, implementation, and evaluation. The subjects in this study were media expert validators, material experts, learning experts, students, and teachers. The results of the development in the form of science-based e-modules are in the form of evaluations from expert validators and trials of students and teachers. The assessment of media experts received a score of 92.85 with the category